(untitled) (Ukrainian Journal of Ophthalmology, 2025)
The monograph presents large science and practice material on studies of the pathogenesis and treatment of ocular burns and their sequelae which has been accumulated for years by the Burn Injury Department (particularly, by the author of the monograph) at the Filatov institute.